소프트달러와 주식형 펀드의 이해상충 - 조성빈 (13063, 2013)
This study analyzes the relationships between soft dollar(brokerage commission) and characteristics of funds, and between brokerage commission and return on funds, using the data on equity funds of Korea from June 2008 to November 2011. The result confirm